Assortment optimization: a systematic literature review - Julia Heger; Robert Klein (OR Spectrum, 2024)
Abstract Assortment optimization is a core topic of demand management that finds application in a broad set of different areas including retail, airline, hotel, and transportation industries as well as in the healthcare sector. Hence, the interest in research on assortment optimization has grown rapidly in recent years. However, the sheer number of publications on the topic of assortment optimization makes it difficult to keep track of all available approaches proposed in the literature. In this paper, we systematically review state-of-the-art studies on assortment optimization. We assemble an extensive literature overview by strategically searching for pre-defined keywords within leading scientific databases. The resulting literature is grouped by a proposed taxonomy that captures properties related to the optimization problem itself, the modelled customer behaviour, and the solution concept applied for solving the problem at hand. For each group, we provide an overview of the corresponding literature and analyse it based on a proposed selection of key factors.
Keywords: 330; Choice modelling; Assortment optimization; Parametric; Nonparametric; Review